Early removal of the etonogestrel contraceptive implant in Spanish women: a prospective cohort study - Ruiz de Viñaspre-Hernández, Regina; Garrido-Santamaria, Rosana; Urra-Martínez, Raquel; Sáenz-Cabredo, Paula; Garrido-Rivas, Ana Elena; Juárez-Vela, Raúl; Sánchez-González, Juan Luis; Lafuente-Jimenez, Alberto; Ramón-Arbués, Enrique; Navas-Echazarreta, Noelia; Santolalla-Arnedo, Ivan (Frontiers in Medicine, 2024)
Purpose To know the discontinuation rate and characterize predictors and reasons of contraceptive implant removal within 12 months of insertion in our community setting. Methods This prospective cohort study included women receiving the etonogestrel contraceptive implant at sexual and reproductive health centers between September 2019 and September 2020. The variables collected were implanted insertion timing, reproductive and demographic characteristics, medical conditions, sexual activity and counseling. Our primary outcome was implant discontinuation. Kaplan–Meier survival curves were used to show the cumulative discontinuation rate of implants contraceptive within the first year of insertion. We also identified factors that increased the risk of implant removal using the log-rank test and the Cox regression model. Reasons for discontinuation were documented. Results 199 women were followed up. Implant discontinuation was documented in 17.1% of implant users prior to 12 months. Factors that increase the risk of implant removal are living with a partner, being aged 25–34 years and not receiving comprehensive and structured counseling from the midwife. The main reason for removal was unsatisfactory bleeding (97.1%), but this was combined with other reasons such as cessation of sexual intercourse (58.8%), worsening mood (58.8%), weight gain (55.9%) or decreased libido (50.0%). Conclusion The rate of discontinuous implant uses in the first year is relevant in relation to cost-effectiveness, there is room for improvement that should not be overlooked. Comprehensive and structured midwife-led counseling can reduce early implant abandonment removal. The development in different countries of the role of midwives in the management of contraceptives can contribute to the economic benefit of health services and the satisfaction of women.